“I was bullied for being fat in every situation, in every outfit, at every celebration”: A qualitative exploratory study on experiences of weight-based oppression in Qatar - O'Hara, Lily; Alajaimi, Bayan; Alshowaikh, Bayan (Frontiers in Public Health, 2023)
Weight-based oppression (WBO) has been documented as a widespread phenomenon in Western countries and is associated with a range of psychological, physiological, and behavioral harms. Research on weight-based oppression is largely absent from the Arab region. We conducted a qualitative exploratory study using semi-structured in-depth interviews to examine the internalized attitudes, values, and beliefs related to body weight, and experiences of external weight-based oppression of 29 staff, faculty, and students at Qatar University. Thematic analysis revealed six major themes on the characteristics of internalized WBO, and the nature, timing, source, extent, and impact of external WBO. WBO was regarded as so common in the Arab culture as to be normative, with damaging exposure to WBO beginning in early childhood. WBO in the Arab region is an important and unrecognized public health issue. Programs to reduce WBO should be developed in all sectors.